Bifidobacteria and Their Molecular Communication with the Immune System - Ruiz, Lorena; Delgado, Susana; Ruas-Madiedo, Patricia; Sánchez, Borja; Margolles, Abelardo (Frontiers in Microbiology, 2017)
Bifidobacterium represents a genus within the phylum Actinobacteria which is one of the major phyla in the healthy intestinal tract of humans. Bifidobacterium is one of the most abundant genera in adults, but its predominance is even more pronounced in infants, especially during lactation, when they can constitute the majority of the total bacterial population. They are one of the pioneering colonizers of the early gut microbiota, and they are known to play important roles in the metabolism of dietary components, otherwise indigestible in the upper parts of the intestine, and in the maturation of the immune system. Bifidobacteria have been shown to interact with human immune cells and to modulate specific pathways, involving innate and adaptive immune processes. In this mini-review, we provide an overview of the current knowledge on the immunomodulatory properties of bifidobacteria and the mechanisms and molecular players underlying these processes, focusing on the corresponding implications for human health. We deal with in vitro models suitable for studying strain-specific immunomodulatory activities. These include peripheral blood mononuclear cells and T cell-mediated immune responses, both effector and regulatory cell responses, as well as the modulation of the phenotype of dendritic cells, among others. Furthermore, preclinical studies, mainly germ-free, gnotobiotic, and conventional murine models, and human clinical trials, are also discussed. Finally, we highlight evidence supporting the immunomodulatory effects of bifidobacterial molecules (proteins and peptides, exopolysaccharides, metabolites, and DNA), as well as the role of bifidobacterial metabolism in maintaining immune homeostasis through cross-feeding mechanisms.